Karakteristik Komite Audit terhadap Kecurangan Laporan Keuangan Perusahaan Properti dan Infrastruktur Indonesia - Bintang Yoga Ramadhani; Ambar Kusumaningsih (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2026)
This study aims to investigate the influence of audit committee characteristics—including the proportion of independent audit committee members, audit committee size, and the frequency of audit committee meetings—on the risk of financial statement fraud in companies in the real estate and infrastructure sectors listed on the Indonesia Stock Exchange from 2020 to 2024. This study is grounded in agency theory and signaling theory. The sample was selected using purposive sampling, involving 62 companies or 310 observations. Data analysis was conducted using multiple linear regression via SPSS version 27. The findings of the study indicate that, collectively, the three audit committee characteristic variables, along with the control variables, have a significant impact on financial statement fraud risk. However, when examined individually, the proportion of independent audit committee members, the size of the audit committee, and the frequency of audit committee meetings do not show an influence. Meanwhile, the profitability control variable (ROA) showed an influence on financial statement fraud risk. This study concludes that the extent to which an audit committee can prevent fraud depends not only on quantitative factors such as the number of members or meeting frequency, but is also more influenced by the quality of the audit committee members’ capabilities and commitment in carrying out their oversight duties.